The Contribution of Bilingualism to Cognitive Functioning and Regional Brain Volume in Normal and Abnormal Aging. Issue 2 (9th March 2022) - Torres, Valeria L.; Rosselli, Mónica; Loewenstein, David A.; Lang, Merike; Vélez-Uribe, Idaly; Arruda, Fernanda; Conniff, Joshua; Curiel, Rosie E.; Greig, Maria T.; Barker, Warren W.; Rodriguez, Miriam J.; Adjouadi, Malek; et al.
Abstract: We examined the association between bilingualism, executive function (EF), and brain volume in older monolinguals and bilinguals who spoke English, Spanish, or both, and were cognitively normal (CN) or diagnosed with Mild Cognitive Impairment (MCI) or dementia. Gray matter volume (GMV) was higher in language and EF brain regions among bilinguals, but no differences were found in memory regions. Neuropsychological performance did not vary across language groups over time; however, bilinguals exhibited reduced Stroop interference and lower scores on Digit Span Backwards and category fluency. Higher scores on Digit Span Backwards were associated with a younger age of English acquisition, and a greater degree of balanced bilingualism was associated with lower scores in category fluency. The initial age of cognitive decline did not differ between language groups. The influence of bilingualism appears to be reflected in increased GMV in language and EF regions, and to a lesser degree, in EF.